Chapter 4 - Destination - J-A. van den Berg (Acta Theologica)
From text: Thematically, and in resonance with the central metaphor of architecture, the last chapter resorts under the design index of destination. In architectonic science, the concept, destination, is defined as “that which we reach”, and implies “the centre of gravity that assembles” (Norberg Schulz 2000:144). Within this broad category of destination, three accents are distinguished in chapter 4, namely orientation, identification and memory.